Випаровування з водної поверхні регулюючих басейнів зрошувальних систем - Рудаков, Леонід Миколайович; Rudakov, Leonid; Гапіч, Геннадій Васильович; Hapich, Gennadiy; Чушкіна, Ірина Вікторівна; Chushkina, Irina (РВВ ДДАЕУ, 2017)
Представлено результати розрахунків випаровування з водної поверхні регулюючих басейнів зрошувальної системи Царичанського міжрайонного управління водного господарства. Проведено порівняння приходної і витратної частин рівняння водного балансу для регулюючих басейнів. Встановлено періоди зниження і підвищення рівнів води в басейнах. Визначено, що за поливний сезон з трьох басейнів загальною площею понад 20 тис. м2 і об’ємом води близько 80 тис. м3 випаровується близько 1 тис. м3 , тобто в середньому 3,5 % від загальних втрат. Інша частина втрат відноситься до фільтраційних, що засвідчує низький рівень коефіцієнта корисної дії системи та незадовільний технічний стан досліджуваних об’єктів. - The article presents materials on water losses determination for evaporation from the water surface of the regulatory pools of irrigation systems using the example of Tsarichanka interregional water management facilities. Nowadays the vast majority of the basic funds of land reclamation systems are subjected to significant wear and tear, and they also require substantial investments to restore them and improve the efficiency. In this case, the primary task is to identify and eliminate unproductive water losses. The authors compared the income and expenditure parts of the water balance equation, as well as the percentage of unproductive water losses for evaporation and filtration. The months in which maximum evaporation values are observed are determined. As a result of calculations it was established that during the irrigation season from three basins with total area of more than 20 thousand m2 and a volume of water of about 80 thousand m3, evaporates about 1 thousand m3, which averages 3,5 % of the total losses. The rest of the losses pertain to filtration, which causes a low technical state of the objects under study.
Evaporation from the water surface of regulating basins of irrigation systems
http://ojs.dsau.dp.ua/index.php/vestnik/article/view/856/818
Keywords: регулюючий басейн; regulating basin; зрошувальна система; irrigation system; випаровування з водної поверхні; evaporation from the water surface; атмосферні опади; atmospheric precipitation; температура повітря; air temperature; втрати води; water loss